The level of self-efficacy in obesity counselling and its associated factors among primary care doctors - Zawawi, Mohamad 'Ariff Fahmi Ahmad (2018)
Introduction: Since its recognition as a disease entity in 1948, obesity is now escalating to a global population pandemic. The latest National Health and Morbidity Survey showed an increasing prevalence of overweight, obesity and abdominal girth since 2006. Without effective interventions, it was estimated that at least half of the world’s adult population will be either overweight or obese by 2030. Primary care doctors are at the forefront of the healthcare system, acting as both patient closest contact personnel and resources manager to organize preventive measures, to control the disease and to manage its comorbidities. However, in clinical practice, available literature highlighted that physicians often perceived themselves to be less confident and less effective in their counselling towards obesity. Objective: The aim of this research was to investigate the level of self efficacy in obesity among primary care doctors and its associated factors. Methodology: This was a cross sectional survey over 151 primary care doctors working in government health clinics in the East Coast of Peninsular Malaysia. Respondents were selected by simple random sampling. An invitation letter was sent to each respondent together with informed consent document. Respondents filled up an online selfadministered questionnaire from 1st December 2016 until 15th January 2017. The data was analysed with descriptive analysis to determine the level of self-efficacy. Multiple linear regression was applied to determine relevant factors associated with the level of selfefficacy in obesity counselling.Results: The response rate of this study was 82.1%. The mean score for self-efficacy in obesity counselling was 66.9% (SD 10.67, 95% CI 65.1, 68.9, p<0.001). From the multivariable analysis, factors found to be associated with the level of self-efficacy include involvement in NCD team (95% CI 0.38, 9.27; p<0.05), formal training on physical activity (95% CI 0.57, 8.48; p<0.05) and knowledge on CPG recommendations (95% CI 0.36, 2.50; p<0.05). Conclusion: This research found that the level of self-efficacy in obesity counselling among primary care doctors was modest. To address this, a structured training program for primary care doctors that emphasize on multidisciplinary and multicomponent obesity care, empowerment of healthy lifestyle intervention and enhancement of knowledge seem to be associated with confidence and perceived effectiveness of obesity counselling.